Game Based Learning Effectiveness with the Kahoot Application Viewed from Learning Interests and Learning Outcomes of Learners in Digital Simulation Subjects - Hasri, Septi Auliya; Basori, Basori; Maryono, Dwi (IJIE (Indonesian Journal of Informatics Education), 2019)
The purpose of this study was to determine whether Kahoot-based game-based learning models can influence learning interest and learning outcomes of participants being educated. Participants from a Vocational School in Surakarta Indonesia were involved in the research. This study used a quasi-experimental method (quasi-experimental design) with pretest-posttest control design. This study used two control and experimental groups. Control with conventional learning and experiment with Kahoot. Data collection is done by distributing questionnaires and learning outcomes tests. The hypothesis test used was a paired sample t-test and independent sample test using the error level of 0.05. The results showed interest in the control class decreased 6.6% and learning outcomes increased by 2.8%. The results of the experimental class study showed interest in learning increased by 6.7% and learning outcomes increased by 9.9%. Hypothesis testing shows the posttest value of both classes' learning interest 0,000 <0,050 and posttest learning outcomes 0,00 <0,05 which means there are differences in the results of the posttest of the two classes. Thus, there are differences and improvements with the use of Kahoot.